In Situ Alloy Formation of a WMoTaNbV Refractory Metal High Entropy Alloy by Laser Powder Bed Fusion (PBF-LB/M) - Huber, Florian; Bartels, Dominic; Schmidt, Michael (Materials, 2021)
High entropy or multi principal element alloys are a promising and relatively young concept for designing alloys. The idea of creating alloys without a single main alloying element opens up a wide space for possible new alloy compositions. High entropy alloys based on refractory metals such as W, Mo, Ta or Nb are of interest for future high temperature applications e.g., in the aerospace or chemical industry. However, producing refractory metal high entropy alloys by conventional metallurgical methods remains challenging. For this reason, the feasibility of laser-based additive manufacturing of the refractory metal high entropy alloy W20Mo20Ta20Nb20V20 by laser powder bed fusion (PBF-LB/M) is investigated in the present work. In-situ alloy formation from mixtures of easily available elemental powders is employed to avoid an expensive atomization of pre-alloyed powder. It is shown that PBF-LB/M of W20Mo20Ta20Nb20V20 is in general possible and that a complete fusion of the powder mixture without a significant number of undissolved particles is achievable by in-situ alloy formation during PBF-LB/M when selecting favorable process parameter combinations. The relative density of the samples with a dimension of 6 × 6 × 6 mm3 reaches, in dependence of the PBF-LB/M parameter set, 99.8%. Electron backscatter diffraction (EBSD) and transmission electron microscopy (TEM) measurements confirm the presence of a single bcc-phase. Scanning electron microscopy (SEM) images show a dendritic and/or cellular microstructure that can, to some extent, be controlled by the PBF-LB/M parameters.<br
Keywords: additive manufacturing; laser powder bed fusion; PBF-LB/M; laser beam melting (LBM); in-situ alloy formation; high entropy alloys (HEA); refractory metals